NatCats and Insurance in a Developing Economy - New Theoretical and Empirical Evidence - Christian Hott; Thi Xuyen Tran (ZBW - Leibniz Information Centre for Economics, 2020)
Our paper analyses the effect of natural catastrophes on insurance demand in a developing economy and the specific role of insurance regulation in this relationship. We base our analysis on a theoretical model as well as a panel regression using household survey level data for Vietnam and corresponding spatial measures of natural catastrophes. Vietnam is especially interesting for our analysis as it is strongly affected by natural catastrophes and experienced an enhancement of insurance regulation in recent years. The theoretical results indicate that a loss experience should have a less positive effect in developing economies than in developed economies. In addition, an enhancement of insurance regulation should make the impact of a loss event on insurance demand more positive. These findings are confirmed in our empirical analysis: Overall natural catastrophes decrease insurance demand of affected households in Vietnam. The enhancement of insurance regulation not only increased insurance demand. It also reversed the effect of natural catastrophes on the property insurance demand of affected households.
Keywords: G22; G52; Q54; 330; Insurance Penetration; Natural Catastrophes; Insurance Regulation